2022
DOI: 10.3390/nano12193282
|View full text |Cite
|
Sign up to set email alerts
|

Structural and Transport Properties of E-Beam Sintered Lanthanide Tungstates and Tungstates-Molybdates

Abstract: Lanthanide tungstates and molybdates are promising materials for hydrogen separation membranes due to their high protonic conductivity. A promising approach to fabricating ceramics based on these materials is radiation thermal sintering. The current work aims at studying the effect of radiation thermal sintering on the structural morphological and transport properties of (Nd,Ln)5.5(W,Mo)O11.25–δ as promising materials for hydrogen separation membranes. The defect fluorite structure was shown to be preserved du… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 41 publications
1
4
0
Order By: Relevance
“…Conventionally sintered bismuth titanates’ samples have larger particles compared to the samples after RTS at 1100 °C ( Figure 6 ). A similar tendency was demonstrated in [ 37 ] for lanthanide tungstates and molybdates. Using the traditional sintering of bismuth titanate at 1100 °C, the average grain size ranges from 1 to 10 microns.…”
Section: Resultssupporting
confidence: 86%
See 4 more Smart Citations
“…Conventionally sintered bismuth titanates’ samples have larger particles compared to the samples after RTS at 1100 °C ( Figure 6 ). A similar tendency was demonstrated in [ 37 ] for lanthanide tungstates and molybdates. Using the traditional sintering of bismuth titanate at 1100 °C, the average grain size ranges from 1 to 10 microns.…”
Section: Resultssupporting
confidence: 86%
“…Hence, it was demonstrated that RTS allows for carrying out sintering processes for shorter times and at lower temperatures compared to those for conventional sintering. Such a difference in sintering temperature and duration required to obtain the desired gas-tightness for radiation–thermal sintering and conventional sintering is apparently related to the dissipation of radiation energy in heterogeneous structures, thermal-diffusional stimulation of mass transfer, and other features of the RTS process [ 37 ].…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations